Sexual dimorphism in stress-induced changes in adrenergic and muscarinic receptor densities in the lung of wild type and corticotropin-releasing hormone-knockout mice - Novakova, Martina; Kvetnansky, Richard; Myslivecek, Jaromir (Stress (Amsterdam, Netherlands), 2010)
We tested the hypothesis that single and repeated immobilization stress affect densities of alpha(1)-adrenoceptor (alpha(1)-AR) and beta-AR subtypes, muscarinic receptors (MR), adenylyl cyclase activity (AC) and phospholipase C activity (PLC) in lungs of male and female wild type (WT) and corticotropin-releasing hormone gene (CRH-knockout (KO)) disrupted mice. We found sex differences in the basal levels of alpha(1)-AR subtypes (females had 2-3 times higher density of receptors than males) and MR (males had twice the density found in females). In marked contrast, beta-AR subtype densities did not differ between sexes. CRH gene disruption decreased all three studied receptors in intact mice (to 20-50% of WT) in both sexes (except beta(1)-AR in females). Stress induced sexually dimorphic responses, while all alpha(1)-AR subtypes decreased in females (to 30% of control approximately), only alpha(1A)-AR level diminished (about 50%) in males. beta(1)-AR decreased in males (to about 40%) but remained stable in females. beta(2)-AR diminished in females (to about 20-60%) and also in males (to about 30-60%). MR decreased in both sexes (approximately to 50%). AC activity diminished in males (to < 50%) while PLC activity was not changed. In CRH-KO mice, the stress response was severely diminished. Paradoxically, the receptor response to stress was less affected by CRH-KO in males than in females. AC activity did not change in CRH-KO mice. In conclusion, in mice the stress reaction is sexually dimorphic and an intact hypothalamo-pituitary-adrenocortical system is required for the normal reaction of pulmonary adrenergic and MR to stress.
Keywords: Male; Receptors, Muscarinic; Receptors, Adrenergic, alpha-1; plíce; Animals; Sex Factors; fyzické omezení; systém hypofýza - nadledviny; beta-adrenergní receptory; Mice; mužské pohlaví; hormon uvolňující kortikotropin; Female; Mice, Knockout; Pituitary-Adrenal System; Restraint, Physical; Receptors, Adrenergic, beta; Stress, Physiological; alfa-1-adrenergní receptory; ženské pohlaví; pohlavní dimorfismus; Sex Characteristics; fyziologický stres; zvířata; receptory muskarinové; myši knockoutované; sexuální faktory; Hypothalamo-Hypophyseal System; systém hypotalamus-hypofýza; Lung; Corticotropin-Releasing Hormone; myši